Juridical Analysis of Shareholder Agreement Letters as a Form of Legal Protection (Research Study in Companies in Batam City) - Purwanti, M. M. Fajar; Fadlan, Fadlan; Nurkhotijah, Siti (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Private companies are one of the main pillars of the national economy in sustainable national development. In carrying out business activities, conflicts often occur between the shareholders of a company. The governance of a company is regulated in Law Number 40 of 2007. The reality of the business world is that often the articles of association in the deed of establishment of a Limited Liability Company as a place to accommodate the clauses agreed to by the shareholders cannot accommodate clauses that are specific to the objectives of the shareholders. shares to manage the running of the Limited Liability Company business they established. This research uses empirical juridical methods. The data used uses secondary data taken as primary data from the collection of laws and regulations relating to the object under study, and secondary and tertiary data from official documents, journals and the internet. Data collection was carried out by means of one-sided questions and answers which was carried out systematically and based on the research objectives. From the results of this research, data was obtained that Limited Liability Companies located in the city of Batam do not pay attention to company governance procedures as regulated in the articles of association in the company's Deed of Establishment, thus providing opportunities for misuse of this trust. Progress in business governance is not well anticipated, which creates gaps in increasing conflict between shareholders in the company. The choice of litigation resolution, which takes a long time and is expensive, is an obstacle to resolving this conflict. The Shareholders' Agreement Letter as a mitigation for future conflict management for the shareholders of a Limited Liability Company should be used from the moment the shareholder's self-binding agreement was made when establishing the company. A shareholder agreement is a legal document that regulates the relationship between the company's shareholders, which concerns their interests or the interests of the Company. Explicitly in UUPT no. 40 of 2007, Article 4 states that this law, the Company's articles of association and other statutory provisions, Article 1320 concerning the validity of agreements, Article 1338 of the Civil Code, binding agreements as law for the founders, applies to the Limited Liability Companies. A shareholder agreement letter is an agreement made in addition to the Articles of Association made by the parties.